Génocide, révisionnisme, négationnisme : la réception contrastée de la série Black Earth Rising - Sylvie Allouche (Cahiers d’histoire.)
Black Earth Rising (Rwanda, la couleur du sang in French) is a 2018 miniseries by Hugo Blick co-produced by the BBC and Netflix whose main character, Kate Ashby, is initially presented as a survivor of the Tutsi genocide which happened in Rwanda in 1994. Adopted following the genocide by a British lawyer, she herself became a lawyer, the series depicting a stage in her life where she finds herself confronted with the complexity of what took place during this period on the political and human levels. However, the series has provoked very contrasting reactions, as we can see through various articles published in recognized newspapers, such as Le Monde or Libération, in online magazines, or in blogs. While some praise the series for its ability to interest the public in a difficult subject, others criticize it for contributing to disseminating a revisionist, and even denialist, version of this historic episode.